Estudiantes afrodescendientes: desafíos en inclusión y acompañamiento en la Universidad Santo Tomás, Bogotá (2021)
This article presents a review of the current process of inclusion of Afro-descendant students at the Universidad Santo Tomás (USTA), Bogota. It is based on the idea that the cultural dimension must be cornerstone in the inclusion of Afro-descendant students to understand their identity, avoid discrimination and racism, and ensure that the inclusion goes beyond economic benefits and allows the incorporation of knowledge of this community in higher education institutions.  A qualitative methodology was implemented, in which institutional documents were reviewed and testimonies were collected from interviews that were later channeled under the categories of ‘racial discrimination / racism’, ‘Afro-descendant identity’ and ‘inclusion’. It was found that, except for the discount policy, to date there are no documents or practices explicitly oriented to the inclusion of the Afro-descendant community in USTA Bogota; however, there is openness from the different instances to build them. Likewise, the interviews revealed differences regarding the concept of ‘Afro-descendant’ and events of racism were voiced that did not have any record or support. It is concluded that there is a need for an institutional agreement on what means to be Afro-descendant and to generated strategies that go beyond quotas or discounts, and favor the identification and attention to symbolic interactions that could produce scenarios of racial discrimination. Inclusion policies for Afro-descendants should respond both to individual needs and to the openness of the University to interact with the historical and cultural contribution of this community.